TREATMENT OF COUGH IN FREQUENTLY ILL CHILDREN WITH ACUTE RESPIRATORY TRACT INFECTIONS - A.I. Safina ("Paediatrician" Publishers LLC, 2014)
Aim: to assess efficacy and tolerability of mucolytic herbal drug in frequently ill children with acute respiratory tract infections. Patients and methods: 54 children diagnosed with «Acute respiratory tract infection associated with dry cough» were included into the study.All children were divided into 2 groups. Patients from both groups received antipyretic agents, decongestants and topical antibiotics. Patients from the 1st group beside the basic treatment received the studied drug. Results: body temperature of the patients fromthe 1st group normalized in shorter period of time; intensity of catarrhal symptoms decreased from the 3d day of disease. Efficacy of treatment of cough in the patients from the 1st group was 98%, in the 2nd - 61%. Conclusions: early indication of the mucolytic herbal drug to frequently ill children allows decreasing not only the rate of relapses of chronic cough but also usage of antibacterial agents.